Analysis of Adverse Effects of Multimodal Gabapentin in Abdominal Wall Reconstruction. Issue 3 (18th January 2022) - Sarac, Benjamin A.; Schoenbrunner, Anna R.; Brower, Kristin I.; Joshi, Girish P.; Janis, Jeffrey E.
Abstract : Background: Multimodal analgesia, a key component of enhanced recovery after surgery protocols, emphasizes the use of nonopioid analgesics. Preoperative and postoperative gabapentin is often included within multimodal analgesia because it has been shown to reduce postoperative opioid use. However, the role of gabapentin has been questioned because of concerns of adverse effects, particularly in the elderly. In an effort to better understand the specific role of gabapentin within the context of an established enhanced recovery after surgery protocol, the authors studied the prevalence of its adverse effects in patients undergoing abdominal wall reconstruction. Methods: Following institutional review board approval, a retrospective review of a prospectively collected database of 267 consecutive patients who underwent abdominal wall reconstruction performed by a single surgeon was conducted. Demographic variables; operative details; postoperative analgesic use; the presence of dizziness, lightheadedness, or altered mental status; hypotension; negative Richmond Agitation Sedation Scale scores; and postoperative falls were recorded and analyzed according to postoperative gabapentin administration. Results: Two hundred thirteen patients (80 percent) met inclusion criteria, of which 138 (65 percent) received postoperative gabapentin. Postoperative gabapentin use was not associated with dizziness, lightheadedness, or altered mental status; hypotension; negative Richmond Agitation Sedation Scale scores; or falls. Furthermore, even among those aged 65 years or older, postoperative gabapentin use was not significantly associated with these adverse events. Conclusions: In patients undergoing abdominal wall reconstruction, postoperative gabapentin administration was not associated with an increase in adverse effects. Further prospective analysis may better allow the characterization of the adverse effects of perioperative gabapentin. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.